2019
DOI: 10.1038/s12276-019-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin ameliorates hepatic ischemia and reperfusion injury through the activation of SIRT-1/FOXO3a-mediated autophagy and mitochondrial biogenesis

Abstract: Hepatic ischemia and reperfusion injury are characterized by impaired autophagy, mitochondrial dysfunction, and subsequent compromise of cellular homeostasis following hepatic surgery or transplantation. Nobiletin, a natural flavonoid, is a beneficial antioxidant that possesses anti-inflammatory and anti-cancer activities. We investigated the effect of nobiletin on hepatic IR injury and described the underlying mechanisms. C57BL/6 mice were subjected to 60 min of partial hepatic ischemia, treated with nobileti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 68 publications
1
77
0
Order By: Relevance
“…To determine the potential mechanism of P2Y2R in regulation of autophagy in DN mice, the expression of p-AKT, p-FOXO3a, p-ULK1, p-Beclin-1 and SIRT-1 were evaluated by western blot analysis. FOXO3a plays a critical role in regulating autophagy in various diseases; in response to stress or pathological conditions, FOXO3a is phosphorylated by AKT and is retained in the cytosol, thereby blocking its transcriptional activity [ 1 , [37] , [38] , [39] ]. Consistently, we found that the levels of phosphorylation in AKT (Ser473) and its substrate FOXO3a (Ser253) were significantly increased in WT DN mice compared to WT control mice, while the levels were decreased in KO DN mice ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the potential mechanism of P2Y2R in regulation of autophagy in DN mice, the expression of p-AKT, p-FOXO3a, p-ULK1, p-Beclin-1 and SIRT-1 were evaluated by western blot analysis. FOXO3a plays a critical role in regulating autophagy in various diseases; in response to stress or pathological conditions, FOXO3a is phosphorylated by AKT and is retained in the cytosol, thereby blocking its transcriptional activity [ 1 , [37] , [38] , [39] ]. Consistently, we found that the levels of phosphorylation in AKT (Ser473) and its substrate FOXO3a (Ser253) were significantly increased in WT DN mice compared to WT control mice, while the levels were decreased in KO DN mice ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SIRT-1 has been assigned to a renoprotective effect by modulating autophagy response through deacetylation of multiple transcription factors including FOXO3a in DN [ 11 , 37 ]. Because SIRT-1 and FOXO3a signalling play a key role in autophagy induction [ 1 , 38 , 40 ], we examined the effect of P2Y2R deficiency on SIRT-1 and FOXO3a expression in DN. The protein and mRNA levels of SIRT-1 and FOXO3a were significantly downregulated in WT DN mice, while the levels were restored in KO DN mice ( Figure 6 A, B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Numerous studies have reported that HD, NIN and NOB are the most potent hepatoprotective ingredients against liver injury induced by clinical ischemia-reperfusion (IR), paraquat (PQ), carrageenan, cyclophosphamide (CYP), carbon tetrachloride (CCl 4 ) and other stimulants [27][28][29][30]. Recently, several studies have revealed that NRG, TN, HT and ED also contribute to the pharmacological effects of AFI in the treatment of liver diseases.…”
Section: Flavonoids In Aurantii Fructus Immaturus and Aurantii Fructusmentioning
confidence: 99%
“…Furthermore, Wu et al explored the protective effects of NOB against IR injury after liver transplantation and found that NOB (50 mg/kg) inhibited the activation of TLR4/NF-κB signaling pathway and the downstream expression of inflammatory mediators in activated Kupffer cells, which then decreased the hepatic infiltration of macrophages and CD4 + lymphocytes, and suppressed liver inflammation [ 27 ]. Recently, it has also been reported that NOB (5 mg/kg) downregulates autophagy-regulatory gene expression, increases forkhead box O3 a (FOXO3a) expression and its nuclear translocation by activating SIRT-1, AKT and PPARγ coactivator-1α (PGC-1α) pathways, which in turn attenuates hepatocyte apoptosis and inflammation in mice with IR injury [ 29 ]. These findings suggest that NOB may possess therapeutic potential for treating liver IR injury or have protective property for liver preservation during transplantation.…”
Section: Pharmacological Effects Of Flavonoids From Afi and Af In LIVmentioning
confidence: 99%